Correction: Efficient multiplexed genome engineering with a polycistronic tRNA and CRISPR guide-RNA reveals an important role of detonator in reproduction of Drosophila melanogaster. - Cristin Chon; Grace Chon; Yurika Matsui; Huiqing Zeng; Zhi-Chun Lai; Aimin Liu (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0245454.].